2010
DOI: 10.1007/s10545-009-9029-2
|View full text |Cite
|
Sign up to set email alerts
|

Storage correction in cells of patients suffering from mucopolysaccharidoses types IIIA and VII after treatment with genistein and other isoflavones

Abstract: Mucopolysaccharidoses are autosomal and recessive lysosomal storage disorders caused by the deficiency of a lysosomal enzyme involved in glycosaminoglycan catabolism. The Sanfilippo type A disease (MPS III A) results from sulfamidase deficiency, which leads to accumulation of heparan sulfate, whereas Sly disease (MPS VII) results from beta-glucuronidase deficiency, leading to accumulation of heparan, dermatan, and chondroitin sulfates. These syndromes are characterized by severe central nervous system degenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 36 publications
7
46
2
Order By: Relevance
“…Therefore, the final effect of genistein action is a decreased efficiency of production of chondroitin/dermatan, heparan, and keratan sulfates. This conclusion is corroborated by the results of earlier biochemical analyses (7,11,36). The altered expression signatures point to inhibition of signaling pathways as important targets for genistein, a candidate for mucopolysaccharidosis-inhibiting agent.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, the final effect of genistein action is a decreased efficiency of production of chondroitin/dermatan, heparan, and keratan sulfates. This conclusion is corroborated by the results of earlier biochemical analyses (7,11,36). The altered expression signatures point to inhibition of signaling pathways as important targets for genistein, a candidate for mucopolysaccharidosis-inhibiting agent.…”
Section: Discussionsupporting
confidence: 67%
“…Some other flavonoids were also able to decrease GAG storage in MPS IIIA, IIIB, and VII cells (Arfi et al 2010;Piotrowska et al 2010;Kloska et al 2011). Similar to rhodamine B, genistein caused a marked improvement in treated MPS IIIB mice, particularly in decreasing GAG storage in various organs (Malinowska et al 2009) and in correction of otherwise severely changed behavior (Malinowska et al 2010).…”
Section: Efficacy Of Srt In In Vitro Studies Experiments With Animalmentioning
confidence: 97%
“…Other isoflavones (formononetin, daidzein, biochanin A, and glycitein) were also effective in decreasing GAG storage in fibroblasts derived from patients suffering from MPS types IIIA and VI (24). Interestingly, combinations of various isoflavones were more effective in reducing GAG storage than any one single isoflavone (24).…”
Section: Experiments With Cell Culturesmentioning
confidence: 97%
“…Other isoflavones (formononetin, daidzein, biochanin A, and glycitein) were also effective in decreasing GAG storage in fibroblasts derived from patients suffering from MPS types IIIA and VI (24). Interestingly, combinations of various isoflavones were more effective in reducing GAG storage than any one single isoflavone (24). This unexpected phenomenon of synergistic action of isoflavones might be explained by results of recent experiments, which indicated that other flavonoids, unlike genistein, can decrease efficiency of GAG synthesis in reactions independent on EGF receptor autophosphorylation (25).…”
Section: Experiments With Cell Culturesmentioning
confidence: 99%